Natural and Mosaic Laws in Philo of Alexandria - Gligorijevic, Kosta (Religion in the Roman empire, 2025)
This paper discusses the relationship between natural law and Philo of Alexandria's code of laws as they are presented in Philo's later works written in Rome in 40-49 ce. In response to recent interpretations, we argue that Mosaic law, as explicated by Philo, is not identical with natural law; instead, Philo considers Mosaic law to only imperfectly share in the authority of natural law, as attested by his descriptions of Mosaic law as a (mere) copy of natural law. The paper thus defends the traditional dichotomy between natural law and Philo's conception of Mosaic law. At the same time, the paper proposes that Philo elucidates the connection between natural law and Mosaic law by using: (i) the Hellenistic concept of the just king, combined with Cicero's concept of rational law, which jointly explain how an unwritten law of nature may appear in incarnate, personified form; and (ii) Plato's account of the acquisition of virtue by means of the study of nature contained in the Timaeus, which shows how extraordinary individuals may assimilate rational norms directly from nature.